CFD approach to investigate the flow characteristics in bi-directional ventilated disc brake - Munisamy K.M.; Yusoff Mohd.Z.; Shuaib N.H.; Thangaraju S.K. (2023)
This paper presents experimental and Computational Fluids Dynamics (CFD) investigations of the flow in ventilated brake discs. Development of an experiment rig with basic measuring devices are detailed out and following a validation study, the possible improvement in the brake cooling can be further analyzed using CFD analysis. The mass flow rate is determined from basic flow measurement technique following that the conventional bi-directional passenger car is simulated using commercial CFD software FLUENT. The CFD simulation is used to investigate the flow characteristics in between blade flow of the bi-directional ventilated disc brake. 2010 American Institute of Physics.